DEVELOPMENT OF A FEM PROCEDURE FOR EVALUATING THE PRESSURE PROFILE IN THE INDUSTRIAL WHEEL AND FATIGUE STRENGTH ANALYSES - Danzi, Nicola; Solazzi, Luigi; Cima, Michele (Journal of Applied Engineering Science, 2024)
Industrial wheels are heavily loaded components that undergo severe cyclic stress conditions. Thus, the design of the rims must include a wide fatigue study which articulates in laboratory and field tests, analytical and numerical analyses and comparison of the experimental and computational results. This paper presents the study approach applied in the study of a 25 in rim for earth-moving machines manufactured by Moveero. The rim was subject to a design update which provided the reduction of the thickness from 11 mm to 9 mm. We decided to study the interaction tire-rim because it’s a critical zone. The failures affected the area of the seat radius of the fixed flange of the rim, which resulted to be the most stressed part of the rim because of the bending actions of the tire on the flange. In order to deepen the cyclic mechanical behaviour of the component, laboratory inflation and rolling tests were carried out in Woodridge USA considering several combinations of inflation pressure and radial load applied to the wheel. The strain data from the tests were analysed to develop a reverse empirical model for the contact pressure between tire and rim. Once the load diagram applied to the flange for each test was estimated, FEM static simulations could be performed on a 3D model of the rim through SolidWorks Simulation. The stress fields obtained were then used for fatigue FEM numerical analyses which could return an evaluation of the predicted life of the component under several load conditions.